ANALYSIS OF THREE CARDIOVASCULAR DRUGS IN THEIR TERNARY MIXTURE USING GREEN ANALYTICAL METHODOLOGY OF SMART SPECTROPHOTOMETRIC METHODS AND RP-HPLC METHOD - Jamal, Marwa K. El; Gazy, Azza A. (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: Development and validation of two new, simple and specific analytical techniques for the simultaneous determination of a ternary mixture of co-administered cardiovascular drugs ticagrelor (TICA), irbesartan (IRB) and hydrochlorothiazide (HCT). Methods: Chemometric assisted UV spectrophotometric methods (considered as green analytical chemistry) and RP-HPLC method were developed and validated. The different applied chemometric methods are based on Fourier function convolution (FF) and Double divisor ratio spectra Fourier function (FFR). As for the HPLC method, it was developed on a C18 SunfireÂ© waters column with a mobile phase composed of Acetonitrile: sodium dihydrogen phosphate (adjusted to pH 3.6 using orthophosphoric acid) in the ratio of 60:40 v/v at a flow rate of 1 ml/min. Quantification was based on measuring peak areas at 230 nm. Results: By applying the chemometric assisted methods, good percentage recoveries were obtained in quantifying each of the drugs in their triple mixture. The RP-HPLC method, peaks were well resolved with retention times 4.6, 8.0 and 10.0 min, for HCT, TICA and IRB, respectively. The established method was also applied in samples spiked with plasma; the peaks were well separated from each other and from plasma protein peaks, proving the ability of the HPLC method to be applied in biological samples. The methods (RP-HPLC and chemometric assisted methods) were validated in terms of linearity, LOD, LOQ, precision and accuracy. The results obtained from the analysis of the co-administered mixture by the proposed chemometric assisted methods were statistically compared to those obtained by the applied RP-HPLC method. Conclusion: The applied RP-HPLC methods were proved to be more sensitive when compared to the applied chemometric methods, thus could be used for determination of drug concentration in human plasma. However, the applied chemometric methods, considered as green analytical chemistry, is a simple, time-saving method that requires minimal use of a hazardous solvent.Â